CASE STUDY: REJUVENATING IMPACT OF THE SKIN K PROTOCOL ON FACIAL AGING - Clauman Goulart , Kyze (Health and Society, 2026)
Facial aging is a multifactorial process associated with structural changes, reduced muscle tone, increased oxidative stress, and the accumulation of cellular metabolic byproducts, such as lipofuscin, impacting skin firmness, uniformity, and luminosity. In 2018, the author developed an original injectable protocol, called Skin K, with a patent application filed, aiming to promote overall improvement in skin quality and facial support through cellular and neuromuscular modulation. Since its implementation in clinical practice, patients undergoing the protocol have been monitored through comparative clinical evaluation and standardized photographic records. Improvements in tissue firmness, greater homogeneity of skin tone, and an overall rejuvenating appearance were observed. The biological mechanisms involved are discussed based on current literature on skin aging. The findings suggest that the protocol may represent a promising approach for improving skin quality and facial support; however, controlled studies are needed for objective validation of the results and in-depth investigation of the mechanisms involved.